A feasibility study of SMART reactor power performance optimizations-part 2: Reflector material selection - Zhong, Yiming; Norman, Paul; Wu, Wenbin (Frontiers in Energy Research, 2022)
The neutron reflector is a general component in the nuclear reactor design. The original SMART reactor design used the coolant water as a reflector surrounding the fission zone. However, this design has low uranium utilization rates in the outermost fuel assemblies, so poor fuel economy. In this study, six potential reflector materials, i.e., heavy water, graphite, beryllium metal and its oxide, steel, and tungsten carbide, have been investigated as the neutron reflector for SMART. Firstly, the materials' cross-sections of neutron scattering and (n,2n) reactions have been cited from ENDF data libraries and analyzed. This analysis found for the neutrons with energy lower than 1 eV, the 9Be atom has six barn elastic scattering cross-sections, and the 9Be(n, 2n)8Be reaction can compensate for neutron leakage. Then, OpenMC is employed to simulate the effect of these reflector materials on power distribution and depletion. Compared with the original design, the beryllium oxide can improve the initial keff from 1.22906 to 1.27446, flat the radial direction power distribution. The analysis on both scales agrees that the beryllium oxide is an efficient neutron reflector choice with good material properties.